Two new deep-water species of squat lobsters (Crustacea: Anomura: Galatheoidea) from the Central and Southwest Indian Ridge - Periasamy, Rengaiyan; Kurian, Palayil John; Ingole, Baban (Zootaxa, 2023)
The high diversity and endemism of benthic species on seamounts are extensively documented. Although the number of squat lobster species from seamount habitats has increased, species from the Central Indian Ridge (CIR) and Southwest Indian Ridge (SWIR) systems remain largely unknown. The hydrothermally active Indian Ridge system harbours potential sites for future Seafloor Massive Sulphides (SMS) mining. Since seabed mining may create a long-lasting impact on the deep-sea ecosystems, it could harm the unique deep-sea life associated with mineral deposits. This study identified two undescribed squat lobster specimens: one from the genus Munidopsis Whiteaves, 1874 from the CIR system in water depths ranging from 1981 to 2033 m, and one from the genus Typhlonida Macpherson & Baba in Machordom, Ahyong, Andreakis, Baba, Buckley, Garcia-Jimenez, McCallum, Rodriguez-Flores & Macpherson, 2022 from the SWIR system in depths ranging from 2070 to 2404 m. Both new species may be distinguished morphologically and genetically based on the partial mitochondrial (mtCOI) gene. To generate baseline environmental and biodiversity data, efforts for accurate sampling and correct identification of biological species are required